Working conditions at schools as perceived by teachers with diverse levels of creative predispositions - Irena Pufal-Struzik (Edukacja Ustawiczna Dorosłych)
An important goal of education is shaping a man with a creative attitude, flexible in action, imaginative, creative, solve problems and see the surrounding world in a holistic and integrated way. Teachers with creative potential and a school providing optimal conditions for the creative functioning of teachers and students are necessary to achieve this goal. The article is an attempt to present the working environment at school from teachers’ perspective (n = 361) taking into account their creativity or unproductivity. Collected data indicates that a significant group of teachers critically evaluate their working environment, and give numerous reasons why the atmosphere at the school does not encourage creativity. Teachers point to disinformation, constant changes that make planning impossible, salary inadequate to workload, lack of time to solve students' problems, limited scope of influence on school’s policy, unrealistic requirements, poor organisational conditions, students’ behaviour, parents’ expectations, lack of support, etc. The research provides valuable implications to use in practice.